Unraveling Narrativity: A Reflexive Paradigm - Raphael, Stuart I. (Current Musicology, 2004)
In the first movement of Haydn’s String Quartet Op. 33, No.5, the V-I cadential gesture revealed at the very outset proves to be a defining struc-tural property throughout the movement. The anachronistic and seemingly impulsive entry of the initial cadence intimates closure, and its successive restatements function as intermittent signposts along the way toward true closure at the end of the movement. Presumably, the listener experiences these recurring gestures as moments of foreshadowing, and navigates through the movement following clear points of reference to arrive at an increasingly predictable resolution. But suppose that the listener instead hears the initial cadence as a more explicit presentation of a future event, as an "effect" known prematurely, or as a goal actualized before its motivation or rationale has been established. In this sense, the listener may hear the closing statement not so much as a subtle foreshadowing suggested in ac-tual time, but rather as an abrupt flash-forwarding to an end point defini-tively announced within implied or imagined time; thus, musical material subsequently heard from that point on works to peel away moments of the present, and to revise the past so as to justify what is already known to be inevitable in the future.